2009
DOI: 10.1007/s00415-009-5165-8
|View full text |Cite
|
Sign up to set email alerts
|

Successive affection of bilateral temporomesial structures in a case of non-paraneoplastic limbic encephalitis demonstrated by serial MRI and FDG-PET

Abstract: Sirs,Non-paraneoplastic limbic encephalitis (NPLE) often results in an unfavorable clinical course with progressive neuropsychological deficits and epileptic seizures despite treatment [1][2][3]. Magnetic resonance imaging (MRI), fluorodeoxyglucose positron emission tomography (FDG-PET) and antibodies against voltage-gated potassium channels (VGKC-Ab) are helpful in monitoring the course of the disease [3][4][5]. We present a follow-up of a NPLE patient over a 3-year period with successive affection of bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
1
9
0
4
Order By: Relevance
“…5 Furthermore, while some authors have indicated that autoimmune VGKC encephalitis may present as a monophasic illness, others have reported progression, with patients shown to develop bilateral temporal lobe involvement with time. 18,19 Our imaging study would support the finding that radiologic progression is common because greater than a quarter (28.6%) of our patients with initially negative study findings or only unilateral findings progressed to bilateral involvement. Whether these changes represent pathology due to persistent CNS inflammation, reflect damage done secondarily by recurrent seizures, or both remains unclear, and prospective longitudinal follow-up will be required to answer this question.…”
Section: Discussionsupporting
confidence: 76%
“…5 Furthermore, while some authors have indicated that autoimmune VGKC encephalitis may present as a monophasic illness, others have reported progression, with patients shown to develop bilateral temporal lobe involvement with time. 18,19 Our imaging study would support the finding that radiologic progression is common because greater than a quarter (28.6%) of our patients with initially negative study findings or only unilateral findings progressed to bilateral involvement. Whether these changes represent pathology due to persistent CNS inflammation, reflect damage done secondarily by recurrent seizures, or both remains unclear, and prospective longitudinal follow-up will be required to answer this question.…”
Section: Discussionsupporting
confidence: 76%
“…PET studies in LE usually report bilateral medial temporal hypermetabolism, as well as hypermetabolism in the frontotemporal lobes, brainstem and cerebellum [11][12][13][14]. Striatal hypermetabolism has, however, been associated Fig.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note that, from these data alone, it is not possible to be certain that the patients’ cognitive improvement was a direct result of treatment, since we do not have a ‘no treatment’ control group. The persistent memory deficits following VGKC-LE are potentially attributable to focal hippocampal atrophy that is often reported after recovery from the acute phase,4 7 11 24 and which may be more common in patients with very high antibody titres 6…”
Section: Discussionmentioning
confidence: 99%